2010
DOI: 10.2166/wst.2010.138
|View full text |Cite
|
Sign up to set email alerts
|

Management of hospital wastewaters: the case of the effluent of a large hospital situated in a small town

Abstract: Hospitals are the main source of pharmaceutical compounds (PhCs) released into the environment. Generally, their discharges are co-treated with domestic wastewaters, resulting in a decrement of the recalcitrant compound concentrations in the final effluent due to water dilution. However, as many PhCs resist normal treatments, pollutant load does not change. This paper compares the chemical characteristics of hospital and domestic wastewaters on the basis of an experimental investigation for macro-pollutants an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 0 publications
2
44
0
2
Order By: Relevance
“…Antibiotics may be impregnated in food given to farm animals and fish and uneaten food contaminates the surrounding environment. Antibiotics from human therapeutic use, especially from hospital effluents, are a continual source of pollution and are considered part of the “emerging contaminants” in municipal waste with concentrations of tetracycline varying from ng/L to μg/L (Verlicchi et al, 2010). At these levels antibiotics may select for antibiotic resistant environmental bacteria which may persist for extended time periods and become reservoirs of antibiotic resistance genes.…”
Section: The Environmentmentioning
confidence: 99%
“…Antibiotics may be impregnated in food given to farm animals and fish and uneaten food contaminates the surrounding environment. Antibiotics from human therapeutic use, especially from hospital effluents, are a continual source of pollution and are considered part of the “emerging contaminants” in municipal waste with concentrations of tetracycline varying from ng/L to μg/L (Verlicchi et al, 2010). At these levels antibiotics may select for antibiotic resistant environmental bacteria which may persist for extended time periods and become reservoirs of antibiotic resistance genes.…”
Section: The Environmentmentioning
confidence: 99%
“…Usually hospital effluents are directly discharged into public sewer network, being co-treated with domestic wastewaters in municipal WWTPs. This practice has been questioned by some authors (Pauwels and Verstraete, 2006;Verlicchi et al, 2012a), who suggested the adoption of a more dedicated treatment for hospital effluents before being discharged into public wastewaters and then both urban and hospital wastewaters would be subsequently treated in WWTPs (Pauwels and Verstraete, 2006;Verlicchi et al, 2010a). This approach has benefits like avoiding the dilution of hospital wastewaters with urban wastewaters, which may result in the inhibition of biomass and reduction of removal efficiency in WWTPs, as well as to avoid losses into the environment due to sewer leakage and combined sewer overflows (Kovalova et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…They are composed of wastewater related to domestic and urban activities, and those specific to hospital practices [1]. Hospital wastewaters contain a variety of toxic and persistent substances such as drug residues, chemical reagents, and disinfectants for medical purposes in a wide range of concentrations, detergents, solvents, revealing and radiographic fixing and radionuclides.…”
Section: Introductionmentioning
confidence: 99%